2017
DOI: 10.1186/s12998-017-0168-5
|View full text |Cite
|
Sign up to set email alerts
|

What are the risks of manual treatment of the spine? A scoping review for clinicians

Abstract: BackgroundCommunicating to patients the risks of manual treatment to the spine is an important, but challenging element of informed consent. This scoping review aimed to characterise and summarise the available literature on risks and to describe implications for clinical practice and research.MethodA methodological framework for scoping reviews was followed. Systematic searches were conducted during June 2017. The quantity, nature and sources of literature were described. Findings of included studies were nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 247 publications
(254 reference statements)
3
56
0
4
Order By: Relevance
“…However, a recent systematic review found inadequate reporting of adverse events with spinal manipulative therapy (SMT), whether catastrophic or otherwise [ 64 ]. Swait and Finch report that serious adverse events with manual treatment of the spine appear to be rare, making it difficult to estimate risk level [ 65 ]. They note that pre-existing pathology may increase the risk of some events and call for enhanced knowledge through clinician use of patient safety incident reporting systems [ 65 ].…”
Section: Defining Levels Of Risk and Informed Consent With Smuamentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent systematic review found inadequate reporting of adverse events with spinal manipulative therapy (SMT), whether catastrophic or otherwise [ 64 ]. Swait and Finch report that serious adverse events with manual treatment of the spine appear to be rare, making it difficult to estimate risk level [ 65 ]. They note that pre-existing pathology may increase the risk of some events and call for enhanced knowledge through clinician use of patient safety incident reporting systems [ 65 ].…”
Section: Defining Levels Of Risk and Informed Consent With Smuamentioning
confidence: 99%
“…Swait and Finch report that serious adverse events with manual treatment of the spine appear to be rare, making it difficult to estimate risk level [ 65 ]. They note that pre-existing pathology may increase the risk of some events and call for enhanced knowledge through clinician use of patient safety incident reporting systems [ 65 ]. Cassidy et al reported no evidence of increased risk of vertebrobasilar artery (VBA) stroke [ 66 ] or carotid artery stroke [ 67 ] associated with chiropractic treatment versus primary care, suggesting coincidental occurrence.…”
Section: Defining Levels Of Risk and Informed Consent With Smuamentioning
confidence: 99%
“…Similar to most health care interventions, adverse events (AEs) have been observed after SMT. Reported post-SMT AEs vary in terms of frequency and severity, ranging from the more frequent minor/benign AEs (such as increased soreness and stiffness) to rare and serious AEs (such as cauda equina syndrome) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies estimated that about 50% of patients receiving SMT experience some kind of AE, most being benign, transient and self-resolving with little to no impact on activities of daily living [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, although several systematic reviews have been conducted to understand the effect of MT in temporomandibular disorders (TMD) and its positive effects have been highlighted, the quality of these studies is now considered low and more and better trials are needed (Armijo-Olivo et al, 2016). A scoping review aiming to understand the risks of manual treatment to the spine, found that benign adverse events following manual treatments were common while serious adverse effects are rare (Swait & Finch., 2017). Although there is some evidence of MT effectiveness, the evidence-informed primary care management of LBP states that there is some evidence to recommend MT as massage therapy and spinal manipulation for prevention and care of LBP (TOP., 2017).…”
Section: Introductionmentioning
confidence: 99%